EXPERIMENTAL STUDY OF DYNAMIC RESPONSE OF THREE-DIMENSIONAL STEEL FRAME ON CORAL FOUNDATION AT THE SONG TU TAY ISLAND - Chung, Nguyen Thai; Binh, Tran Van; Thuy, Le Xuan; Anh, Le Hoang (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents some results of experimental study of dynamic response of three- dimensional steel frame on coral foundation at the Song Tu Tay Island subjected to pulsed loads. This is one of the contents of the project with code KC.09.26/11-15 corried out by the survey, experiments on the Song Tu Tay island of the Truong Sa archipelago of Vietnam. The findings by the authors were compared with the results of theoretical calculations to examine the appropriateness of the model and theoretical research methods, to give assessments, comments having scientific and applied meanings, especially for the construction of structures on the Shoals around atolls of the Truong Sa archipelago.